Friends like this: The impact of the US-China trade war on global value chains - Haiou Mao; Holger Görg (Kiel Centre for Globalization (KCG), 2019)
This paper considers the indirect impact the recent tariff increases between the US and China can have in third countries through links in global supply chains. We combine data from input-output relationships, imports and tariffs, to calculate the impact of the tariff increases by both the US and China on cumulative tariffs for other countries and thus hurt trade partners further downstream in global supply chains. We also show that this is particularly important for tariff increases on Chinese imports in the US. These are likely to be used as intermediates in production in the US, which are then re-exported to third countries. The most heavily hit third countries are the closest trade partners, namely Canada and Mexiko. We estimate that the tariffs impose additional burden of around 500 to 600 million US dollars on these two countries. China's tariffs on US imports have less of an effect.
Keywords: F1; 330; trade war; cumulative tariffs; indirect tariffs